Good Cop, Bad Cop: The Different Roles of SRPKs - Nikolakaki, Eleni; Sigala, Ioanna; Giannakouros, Thomas (Frontiers in Genetics, 2022)
SR Protein Kinases (SRPKs), discovered approximately thirty years ago, are widely known as splice factor kinases due to their decisive involvement in the regulation of various steps of mRNA splicing. However, they were also shown to regulate diverse cellular activities by phosphorylation of serine residues residing in serine-arginine/arginine-serine dipeptide motifs. Over the last decade, SRPK1 has been reported as both tumor suppressor and promoter, depending on the cellular context and has been implicated in both chemotherapy sensitivity and resistance. Moreover, SRPK2 has been reported to exhibit contradictory functions in different cell contexts promoting either apoptosis or tumor growth. The aim of the current review is to broaden and deepen our understanding of the SRPK function focusing on the subcellular localization of the kinases. There is ample evidence that the balance between cytoplasmic and nuclear SRPK levels is tightly regulated and determines cell response to external signals. Specific cell states coupled to kinase levels, spatial specific interactions with substrates but also changes in the extent of phosphorylation that allow SRPKs to exhibit a rheostat-like control on their substrates, could decide the proliferative or antiproliferative role of SRPKs.